Beyond idols : the shape of a secular society - Fenn, Richard K. (Oxford University Press, 2001)
This study attempts to articulate the nature of a secular society, describe its benefits, and suggest the conditions under which such a society could emerge. To become secular, argues Fenn, is to open oneself to a wide range of possibilities.